Exploring the Legal and Contractual Impediments in BIM-based Application: A Systematic Literature Review - Sharifah Nur Aina Syed Alwee; Noor Akmal Adillah Ismail; Umi Kalsum Zolkafli @ Zulkifly; Salleh, Hafez; Abd. Jamil, Ahmad Huzaimi (International Journal of Sustainable Construction Engineering and Technology, 2024)
Building information modelling (BIM) has been theoretically proven to enhance the integration of design, construction, and operation processes, hence improving the holistic delivery of a construction project. Despite the many initiatives provided by the government across various countries to increase the uptake of BIM in project implementation, previous studies have discovered the many barriers to successfully applying BIM, among which are legal and contractual issues. Hence, the present study explores and reviews the current legal and contractual impediments that have restricted BIM-based applications in the construction industry. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were employed as a standard protocol for reviewing the current research in the existing literature. The overall search process resulted in a total of 44 articles, which were then thematically analysed to disclose the findings. The review derived eight key aspects, namely procurement method, contract documentation, time and cost, quality, coordination, liability, security and law and regulation and their respective subcomponents as the basis of legal and contractual impediments that could challenge the success of BIM application in construction projects. The study extends the existing knowledge of BIM application and the implications arising from its utilisation and offers some practical insights for design and construction practitioners to improve their roles, obligations, and compliance with BIM contractual requirements. Several recommendations are also made for future research on BIM functionalities for contract administration.